2020
DOI: 10.1016/j.jesp.2020.104025
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to ingroup and outgroup norms in the association between commonality and morality

Abstract: Emerging research suggests that people infer that common behaviors are moral and vice versa. The studies presented here investigated the role of group membership in inferences regarding commonality and morality. In Study 1, participants expected a target character to infer that behaviors that were common among their ingroup were particularly moral. However, the extent to which behaviors were common among the target character's outgroup did not influence expectations regarding perceptions of morality. Study 2 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 60 publications
2
16
0
Order By: Relevance
“…Even though participants became more honest after observing an honest out-group member, they failed to positively judge such moral virtuosity. Instead, an outgroup member's honesty was perceived as on par with a dishonest ingroup member, conceptually replicating the general phenomenon that people perceive in-group behavior as more indicative of morality than the same behaviors from an out-group member (Goldring & Heiphetz, 2020). This parallels the daily moral contortions observed in the news and on social media, where people are quick to condone immoralities committed by their own political party but easily overlook the moral acts endorsed by the opposing party.…”
supporting
confidence: 54%
“…Even though participants became more honest after observing an honest out-group member, they failed to positively judge such moral virtuosity. Instead, an outgroup member's honesty was perceived as on par with a dishonest ingroup member, conceptually replicating the general phenomenon that people perceive in-group behavior as more indicative of morality than the same behaviors from an out-group member (Goldring & Heiphetz, 2020). This parallels the daily moral contortions observed in the news and on social media, where people are quick to condone immoralities committed by their own political party but easily overlook the moral acts endorsed by the opposing party.…”
supporting
confidence: 54%
“…This implies that within the social identity framework, the distinction between descriptive and injunctive norms is less clear: Behaviors that are common among ingroup members not only describe behavior but also prescribe it, because they tell members how they should behave to fit in (Hogg & Reid, 2006). For example, a recent study by Goldring and Heiphetz (2020) found that the more common people believe that certain behaviors are in the ingroup, the more moral they perceive these behaviors to be (and this effect was not as prominent for the outgroup). The tendency to be influenced by perceptions of what others do should therefore be especially likely when one identifies with, or feels similar to, the (norm) reference group (Christensen et al, 2004).…”
Section: The Importance Of Similarity To the Reference Groupmentioning
confidence: 99%
“…Such essentialist thought is also associated with negative outcomes including prejudice and stereotypes (e.g., Chen & Ratliff, 2018). Further, combined with people's tendency to conflate "what it is" with "what ought to be" (Roberts et al, 2017), these forms of reasoning may cause stronger negativity towards non-typical category members because the norms they violate are treated as innate and critical features of the category membership, perhaps especially towards ingroup members (Goldring & Heiphetz, 2020).…”
Section: Non-structural Reasoning About Social Categoriesmentioning
confidence: 99%